The Open Government Data Policy as a Strategic Use of Information to Entrench Neoliberalism? The Case of Italy - Laura Franceschetti (Partecipazione e Conflitto, 2016)
The philosophy of Open Government provides a new paradigm of innovation in public admin-istration built around three key words: transparency, participation and collaboration. Greater transparency of information about the PA and its way of working should help to regain public confidence in the institu-tions, motivating people to take a more active part in decision making processes. It should also encourage them to support the institutions by inputting their own knowledge and abilities, consequently engendering a widespread spirit of collaboration between different public authorities and between them and the pub-lic, businesses and non profit organisations, in order to relaunching the economic value of the Public Sec-tor Information (Huijboom, Van den Broek, 2011). The hypothesis behind this contribution, starting from an approach based on an interpretation of significant elements in public action (Moini 2013) and of their conceptual framework (Fischer 2003), is that through which open government, open data, social media, collective intelligence, and connectivity are key words in a new rhetoric of administrative innovation - summed up in the label ‘’government 2.0’’ - which refers to a form of public action easily seen to be drawn from the neoliberal paradigm (Jessop, 2002), even though subject to some variegated form at na-tional level